Goodbye, Paris : a novel - Harris, Anstey (Touchstone, 2018)
Grace once had the beginnings of a promising musical career, but she hasn<U+2019>t been able to play her cello publicly since a traumatic event at music college years ago. Since then, she<U+2019>s built a quiet life for herself in her small English village, repairing instruments and nurturing her long- distance affair with David, the man who has helped her rebuild her life even as she puts her dreams of a family on hold until his children are old enough for him to leave his loveless marriage. But when David saves the life of a woman in the Paris Metro, his resulting fame shines a light onto the real state of the relationship(s) in his life. Shattered, Grace hits rock bottom and abandons everything that has been important to her, including her dream of entering and winning the world<U+2019>s most important violin-making competition. Her closest friends<U+2014>a charming elderly violinist with a secret love affair of his own, and her store clerk, a gifted but angst-ridden teenage girl<U+2014>step in to help, but will their friendship be enough to help her pick up the pieces?